CHOOSING THE OPTIMAL TREATMENT METHOD IN PATIENTS WITH APICAL PERIODONTITIS - Aliyev, B.F. (World of Medicine and Biology, 2022)
The article provides information on choosing the optimal treatment method in patients with apical periodontitis, taking into account the nature of the inflammatory changes in the periapical dental tissues. 120 patients with different forms of apical periodontitis were examined and 3 groups were formed from them. “Closed” and “opened” treatment methods for apical periodontitis were used for the patients diagnosed with acute apical periodontitis and periapical abscess, and both therapeutic and surgical treatment methods were used for the patients with complications of apical periodontitis, i.e. with acute periostitis and osteomyelitis. In patients of the group where the “closed” treatment method of apical periodontitis was used, the periapical index decreased from 2.77±0.136 to 1.20±0.114 points and from 2.50±0.133 to 1.57±0.114 points; in patients of the group where the “opened” treatment method of apical periodontitis was used, it decreased from 2.55±0.185 to 1.80±0.117 points. In patients with complications of apical periodontitis, compared to the previous groups, the periapical index decreased slightly and amounted to 2.06±0.117 points. Thus, research has shown that more reliable treatment methods were as follows: “closed” and “opened” treatment methods of apical periodontitis during the development of acute apical periodontitis and periapical abscess, and conservative and surgical intervention in the treatment of both acute periostitis and acute osteomyelitis.
Keywords: acute apical periodontitis; periapical abscess; acute periostitis; focus of periapical destruction; periapical index; treatment of acute apical periodontitis; redness of mucous membrane